EVALUATION OF THE PREDICTIVE ABILITY OF THE MANNHEIM PERITONITIS INDEX (MPI) IN PATIENTS WITH SECONDARY PERITONITIS (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Secondary peritonitis is a major cause of morbidity and mortality worldwide, particularly in resource-limited settings. Several prognostic scoring systems have been developed to predict outcomes in patients with secondary peritonitis, among which the Mannheim Peritonitis Index (MPI) is widely used due to its simplicity and reliance on eight readily assessable prognostic variables. Objective: To evaluate the predictive ability of the Mannheim Peritonitis Index in patients with secondary peritonitis. Study Design: Observational study. Duration and Place of Study: This study was conducted at People’s University of Medical and Health Sciences Nawabshah Pakistan from March 2025 to March 2026 Methodology: This observational study was conducted in the Department of Surgery and included 120 patients with surgically confirmed secondary peritonitis. Patients aged 18 years and above were enrolled. Clinical, laboratory, and intraoperative findings were recorded for all participants. The MPI score was calculated for each patient and used to stratify patients according to risk. Morbidity and mortality outcomes were assessed over a 30-day follow-up period. Statistical analysis was performed using SPSS. Associations between MPI scores and clinical outcomes were evaluated using the Chi-square test and receiver operating characteristic (ROC) curve analysis. Results: A total of 120 patients were included, comprising 88 (73.3%) males and 32 (26.7%) females. The majority of patients belonged to the younger age group (verify age range and frequency), accounting for 55% (n=66) of the study population. Generalized peritonitis was present in 98 (81.7%) patients. Delayed presentation and preoperative shock were observed in 112 (93.3%) patients. The overall mortality rate was 12.5% (n=15). Mortality was significantly higher among patients older than 50 years, with 11 deaths occurring in this age group. Higher MPI scores were associated with increased morbidity and mortality. Conclusion: The Mannheim Peritonitis Index is a valuable and reliable prognostic tool for predicting morbidity and mortality in patients with secondary peritonitis. Higher MPI scores are associated with poorer clinical outcomes and may assist clinicians in risk stratification and management planning.